Five-year trends in antimicrobial susceptibility of uropathogens isolated from paediatric patients attending a tertiary care teaching hospital - Surlu, Vidya Rao; Krishnan, Ashwi R.; Edavaloth, Preethy; Mankarathodi, Arshad Jaman; Neliyathodi, Fysal; Jakribettu, Ramakrishna Pai (International Journal of Contemporary Pediatrics, 2024)
Background: Urinary tract infection (UTI) is a common bacterial infection encountered by paediatrician in their routine clinical practice, globally. To avoid complications, accurate diagnosis and initiation of appropriate antimicrobial therapy is very important. To reduce the treatment failure, the change in antimicrobial resistance (AMR) pattern is very essential. Aim was to study the trend of antimicrobial susceptibility of uropathogen in paediatric patients attending the tertiary care hospital. Methods: It was a retrospective study conducted in the department of microbiology, paediatrics and quality control, the records of paediatric patients i.e., between 1-16 years age, diagnosed with UTI between January 2017-December 2021 were collected. The age, gender, uropathogens and their antimicrobial susceptibility were noted. The data was analysed by frequency and percentage. Results: A total of 276 paediatric patients were diagnosed with UTI during the study period. The highest number of patients i.e., 109/276 (39.5%) belonged between 1-5 years of age with female predominance. E. coli (148/ 276, 53.62%) was the most common uropathogen isolated followed by Klebsiella spp. (57/276, 20.7%). Staphylococcus spp. and Enterococcus spp. were the common Gram-positive pathogens. Highest resistance was observed to ampicillin followed by 3rd generation cephalosporin (3GC), folate inhibitors among the E. coli and similarly in Klebsiella isolates. There was increasing rate of resistance seen in ampicillin, 3GC, nitrofurantoin, beta lactum-beta lactamase inhibitor combination. Conclusions: E. coli is the most common cause of UTI with changing resistance pattern over five years. So, the antibiogram needs to be closely monitored and the AMA for empirical therapy needs modified annually.